Development and Validation of "Merdeka": An Augmented Reality-Based Board Game for Indonesian History Learning - Dewi, Grace Levina; Setiawan, Mikhael; Prayogi, Alan David (Jurnal Paedagogy, 2026)
This study aims to develop and evaluate the feasibility of an educational board game, Merdeka, integrated with Augmented Reality (AR) technology as a history learning medium for junior high school students aged 13–15 years. The study employed a development research method using the Game Development Life Cycle (GDLC) model, which consists of six stages: initiation, pre-production, production, alpha testing, beta testing, and release. The feasibility of the product was assessed using a three-pronged evaluation approach: validation by material and media experts, black-box functionality testing of the AR application, and a limited beta trial involving 24 junior high school students. Data were analyzed using descriptive quantitative techniques based on Likert-scale scoring. The expert validation results indicated a “highly feasible” category, with average feasibility scores of 89.44% from material experts and 85.71% from media experts. The user trial results also demonstrated a very high level of acceptance, achieving a feasibility score of 84.8%. These findings indicate that the enjoyable gameplay experience and the integration of AR technology constitute the primary strengths of the product. In conclusion, the Merdeka educational board game is a valid, functional, and well-received learning medium and is therefore suitable for implementation and broader dissemination.